Marketing Efficiency Analysis of Oil Palm Fresh Fruit Bunches (FFB) in Independent Smallholders in Mandiangin District Sarolangun Regency - Mindo Tampubolon; Saidin Nainggolan (Politeknik Pertanian Negeri Samarinda, 2026)
The purpose of this study is to investigate the marketing strategies and marketing effectiveness of fresh palm fruit (FFB) grown by independent smallholder farmers in Sarolangun Regency's Mandiangin area. The study location was chosen because Mandiangin's palm FFB distribution method involves multiple different marketing channels. The research involved 45 purposively selected respondents, with data collected through questionnaires distributed to independent farmers as well as related marketing institutions. The analysis was carried out by applying several indicators, including technical and economic efficiency indices, marketing costs, marketing margins, farmers’ share, and overall marketing efficiency. The findings show that there are four marketing channels for palm FFB in the study area, which involve collection points (RAM) and middlemen (toke). Among the four channels, Channel IV shows the highest level of economic efficiency, characterized by a marketing margin of IDR 0/kg, a farmer’s share of 100%, and an economic efficiency index of 4.55 IDR/kg. In contrast, Channel III demonstrates the highest technical efficiency, with a technical efficiency value of 14,29 IDR/kg/km. Furthermore, the MANOVA results reveal statistically significant differences in marketing efficiency across the four channels when assessed based on both technical and economic efficiency indicators.